A rapid and easy protein N‐terminal profiling strategy using (N‐Succinimidyloxycarbonylmethyl)tris(2, 4, 6‐trimethoxyphenyl)phosphonium bromide (TMPP) labeling and StageTip. Issue 13 (3rd July 2017) - Li, Yanchang; Wang, Zhiqiang; Zhou, Wenjing; Zhang, Kun; Ma, Jie; Wu, Feilin; Ji, Jianguo; Hong, Xuechuan; Deng, Zixin; He, Simin; Xu, Ping
Abstract : Protein N‐terminal profiling is crucial when characterizing biological functions and provides proteomic evidences for genome reannotations. However, most of the current N‐terminal enrichment approaches involve multiple chemical derivatizations and chromatographic separation processes which are time consuming and can contribute to N‐terminal peptide losses. In this study, a fast, one‐step approach utilizing (N‐Succinimidyloxycarbonylmethyl)tris(2, 4, 6‐trimethoxyphenyl)phosphonium bromide (TMPP) derivatization and StageTip separation was developed to enhance N‐terminal peptide enrichment and analysis. Based on the characteristics of TMPP‐derivatized samples, such as a higher hydrophobicity and increased likelihood to produce a and b ions in collision‐induced dissociation or HCD fragmentation modes, first the SDS‐PAGE was optimized to increase protein loading and gel entry and to remove unbound TMPP. Then, this process was combined with a simplified StageTip separation and a new scoring criterion (considering a, b and y ions) to identify more TMPP‐modified N‐terminal spectra. When utilizing a low amount of starting material (∼20 μg protein), a total of 581 yeast N‐terminal peptides were identified, with 485 of them being TMPP modified, in only about one third of the general experimental time. It is hoped that the workflow constructed herein will provide a fast and practical strategy for N‐terminomic studies.